2001
DOI: 10.1023/a:1013617232576
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Eleven novel analogs of 2-deoxy-2,3-didehydro-N-acetylneuraminic acid (Neu5Ac2en) modified at the C-4 and C-9 positions were designed and tested for their ability to inhibit sialidase of human parainfluenza virus type 1 (hPIV-1). The analogs modified by the cyanomethyl, amidinomethyl, and thiocarbamoylmethyl groups at the C-4 position exhibited potent inhibition against hPIV-1 sialidase compared with Neu5Ac2en. The most effective compound was thiocarbamoylmethyl analog (4-O-thiocarbamoylmethyl-Neu5Ac2en). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The multifunctionality of hPIV HN makes it a target of choice for the design of antiviral drugs. Several inhibitors based on the 2-deoxy-2,3-didehydro-D- N -acetylneuraminic acid (Neu5Ac2en, 1 ) scaffold, such as BCX 2798 ( 2 ) [7,8] (Figure 1A), have been designed to target hPIV-1 HN’s catalytic domain, but none have advanced to clinical studies [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The multifunctionality of hPIV HN makes it a target of choice for the design of antiviral drugs. Several inhibitors based on the 2-deoxy-2,3-didehydro-D- N -acetylneuraminic acid (Neu5Ac2en, 1 ) scaffold, such as BCX 2798 ( 2 ) [7,8] (Figure 1A), have been designed to target hPIV-1 HN’s catalytic domain, but none have advanced to clinical studies [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The spread of paramyxoviruses in tissues depends on the efficient release of viral progeny from primary infected cells, leading to further cell infections. NA inhibitors are applied extracellularly to inhibit that viral spread to neighboring cells [1, 38]. When, as shown with our mutants, receptor inactivation and receptor destruction are already finished before the process of virus budding has started, the effects of antiviral drugs should be rather directed toward preventing paramyxoviral progeny from adsorption to new, uninfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Portner et al reported that compounds BCX 2798 (3) and BCX 2855 (4) with modifications at C-4 and C-5 positions of 1, which were designs based on the crystal structure of the HN of Newcastle disease virus (NDV), were specific and potent inhibitors of hPIVs. 10) We demonstrated that 4-O-amidinomethyl-5, 11,12) 4-O-thiocarbamamoylmethyl-6, [11][12][13] 4-O-ethyl-7, 14) and 4-O-(2-thienyl-2-propynyl) Neu5Ac2en derivatives 8 15) have potential inhibitory activities against the sialidase from hPIV-1.…”
Section: 2)mentioning
confidence: 99%